Combating Antibiotic Resistance: Mechanisms, Multidrug-Resistant Pathogens, and Novel Therapeutic Approaches: An Updated Review - Mostafa E. Elshobary; Nadia K. Badawy; Yara Ashraf; Asmaa A. Zatioun; Hagar H. Masriya; Mohamed M. Ammar; Nourhan A. Mohamed; Sohaila Mourad; Abdelrahman M. Assy (Pharmaceuticals)
The escalating global health crisis of antibiotic resistance, driven by the rapid emergence of multidrug-resistant (MDR) bacterial pathogens, necessitates urgent and innovative countermeasures. This review comprehensively examines the diverse mechanisms employed by bacteria to evade antibiotic action, including alterations in cell membrane permeability, efflux pump overexpression, biofilm formation, target site modifications, and the enzymatic degradation of antibiotics. Specific focus is given to membrane transport systems such as ATP-binding cassette (ABC) transporters, resistance–nodulation–division (RND) efflux pumps, major facilitator superfamily (MFS) transporters, multidrug and toxic compound extrusion (MATE) systems, small multidrug resistance (SMR) families, and proteobacterial antimicrobial compound efflux (PACE) families. Additionally, the review explores the global burden of MDR pathogens and evaluates emerging therapeutic strategies, including quorum quenching (QQ), probiotics, postbiotics, synbiotics, antimicrobial peptides (AMPs), stem cell applications, immunotherapy, antibacterial photodynamic therapy (aPDT), and bacteriophage. Furthermore, this review discusses novel antimicrobial agents, such as animal-venom-derived compounds and nanobiotics, as promising alternatives to conventional antibiotics. The interplay between clustered regularly interspaced short palindromic repeats (CRISPR) and CRISPR-associated proteins (Cas) in bacterial adaptive immunity is analyzed, revealing opportunities for targeted genetic interventions. By synthesizing current advancements and emerging strategies, this review underscores the necessity of interdisciplinary collaboration among biomedical scientists, researchers, and the pharmaceutical industry to drive the development of novel antibacterial agents. Ultimately, this comprehensive analysis provides a roadmap for future research, emphasizing the urgent need for sustainable and cooperative approaches to combat antibiotic resistance and safeguard global health.